2021
DOI: 10.1111/aor.14156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adaptive gastric electrical stimulation on weight, food intake, and food intake rate in dogs

Abstract: Background: Gastric electrical stimulation (GES) has been studied for decades as a promising treatment for obesity. Stimulation pulses with fixed amplitude and pulse width are usually applied, but these have limitations with regard to overcoming habituation to GES and inter-subject variation. This study aims to analyze the efficacy of an adaptive GES protocol for reducing food intake and maintaining lean weight in dogs.Methods: Six beagle dogs were implanted with a remotely programmable gastric stimulator. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For instance, several teams have proposed implantable bladder pressure measurement systems (Majerus et al 2017, Weydts et al 2017, Soebadi et al 2019, 2020. Others have proposed anchoring methods (Debelle et al 2021(Debelle et al , 2022 or suturing methods (Koldewijn et al 1994, Walter et al 2022 that could be used to secure small implants to the bladder, which remains a challenge (Basu et al 2019). These approaches would allow the detection of bladder contractions and the measurement of rising intravesical pressure or urine volume, enabling voiding and incontinence anticipation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several teams have proposed implantable bladder pressure measurement systems (Majerus et al 2017, Weydts et al 2017, Soebadi et al 2019, 2020. Others have proposed anchoring methods (Debelle et al 2021(Debelle et al , 2022 or suturing methods (Koldewijn et al 1994, Walter et al 2022 that could be used to secure small implants to the bladder, which remains a challenge (Basu et al 2019). These approaches would allow the detection of bladder contractions and the measurement of rising intravesical pressure or urine volume, enabling voiding and incontinence anticipation.…”
Section: Discussionmentioning
confidence: 99%
“…Using 30 Hz, 30-s-on, 5-min-off bilateral sVNS in pigs, Malbert et al demonstrated that pulsons decreased daily energy consumption, particularly of high-fat diet, whereas both pulsons and more traditional sVNS reduced consumption of a high-glucose diet [ 32 ]. In a recent study, Debelle et al demonstrated that using a dynamic and adaptive stimulation reduced food intake and hence caloric intake, ultimately reducing body weight in dogs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…VNS has been associated with reduced plasma glucose, cholesterol, visceral fat, and blood pressure [ 34 ]. Studies have shown reduced food intake during VNS [ 32 , 35 38 ]. Recently, an elegant study utilizing optogenetics suggested that activation of axons that innervate stomach and intestinal stretch mechanoreceptors is the primary factor that reduces food consumption [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second category of recording techniques primarily encompasses the recording of muscular electrical behavior, named electromyography (EMG) [8], and impedance variation resulting from stomach distension or contraction [15]. These techniques have also proved efficacy in dog models and in humans [20], [21]. However, the monitoring of electrical signals is susceptible to external interference, such as the current delivered by a gastric stimulator, giving rise to artifacts that can saturate the recording electrodes.…”
Section: Introductionmentioning
confidence: 99%